EFFECTS OF LEISURE PROGRAM ON WELL-BEING OF JUNIOR HIGH SCHOOL STUDENTS - Phetdaeng, Chomwart; Tangsujjapoj, Suvimol; Polsor, Kalapruet (Academic Journal of Thailand National Sports University, 2022)
The objective of this quasi - experimental research was to study the effects of leisure program on the well - being of junior high school students. Samples were 60 students of Anuban Muang Chumphon Watsubannimit School who were selected by wellbeing evaluation, and then match-paired sampling into experimental and control groups (30 for each). The research instruments were: - 1) the well - being evaluation questionnaire - the content validity was approved by 5 leisure experts (IOC = 0.8 - 1.0) as well as the Cronbach alpha coefficient correlation reliability was 0.88, and 2) the leisure program - the face validity was in the most appropriate level. Data were analyzed by using mean, standard deviation, and t - test. The findings were found that: - 1) after the experimental group attending the 8 - week leisure program, there were more wellbeing than before attending at the statistic of .05; and 2) after attending the 8 - week leisure program, the experimental group had more well-being than the control group at .05. It can be concluded that the leisure program affected the wellbeing of junior high school students. It possesses appropriateness to application.